Primary Intravitreal Bevacizumab Injection in Macular Eudema Due to Branched Retinal Vein Occlusion - Yalçın, Ahmet; Bucak, Yasin Yücel; Kükner, Ahmet Şahap; Serin, Didem; Özmen, Sedat (Fırat University, 2011)
Objective: To evaluate the effectiveness of primary intravitreal bevacizumab (IVB) injection in macular edema due to branched retinal vein occlusion (BRVO). Materials and Methods: Twelve eyes of 12 patients with macular edema due to BRVO were included in the study. Macular edema, hemorrhage and decreased visual acuity due to BRVO were observed in all patients. Patients who have had not take any prior treatment because of BRVO were involved in the study.Fundus fluorecein angiography was taken before injection in all patients. Intravitreal injection of 1.25mg/0.05ml bevacizumab was performed in all patients. Visual acuity, fundus findings, and complications were recorded before and after injection. Results: Eight patients were women and 4 patients were men. Mean age of the subjects was 59.5 years (22-76 years). Single IVB injection was performed in all patients. The time interval between the BRVO development and IVB injection was 23.9 days (5-75 days). Mean follow up was 134.5 days (16–570 days). Mean visual acuities were 0.9±0.4 and 0.3±0.3 LogMAR before injection and on the last follow up visit after injection, respectively (p

Amaç: Retina ven dal tıkanıklığına (RVDT) bağlı maküla ödemi olan hastalarda primer tedavi olarak intravitreal bevakizumab (İVB) enjek-siyonunun etkinliğini değerlendirmek. Gereç ve Yöntem: RVDT'ye bağlı maküla ödemi olan 12 hastanın 12 gözü çalışmaya alındı. Hastaların hepsinde RVDT'ye bağlı makülada ödem, hemoraji ve görme keskinliğinde azalma mevcuttu. Daha önce herhangi bir tedavi almamış olan hastalar çalışmaya alındı. Enjeksiyon öncesi tüm hastalara fundus floresein anjiografi (FFA) çekildi. Tüm hastalara intravitreal 1,25mg/0,05ml bevakizumab enjeksiyonu yapıldı. Enjeksiyon öncesi ve sonrası görme keskinliği, fundus bulguları ve komplikasyonlar kaydedildi. Bulgular: Hastaların 8'i kadın, 4'ü erkekti. Yaş ortalamaları 59,4 yıl (22-76 yıl) idi. Tüm hastalara tek enjeksiyon yapıldı. RVDT gelişmesi ile IVB enjeksiyonu arasında geçen ortalama süre 23,9 gün (5 -75 gün) idi. Hastaların ortalama takip süresi 134,5 gün (16–570 gün) idi. Enjeksiyon öncesi ortalama görme keskinliği 0,9±0,4 ve enjeksiyon sonrası son takipte görme keskinliği 0,3 ± 0,3 LogMAR idi (p
Retina Ven Dal Tıkanıklığına Bağlı Maküla Ödeminde Primer Intravitreal Bevakizumab Enjeksiyonu